EXAMINING THE RELATIONSHIP BETWEEN FOREIGN PURCHASE LIBERALISATION AND HOUSING AFFORDABILITY - Zull Kepili, Ema Izati (International Journal of Property Sciences (E-ISSN: 2229-8568), 2020)
This study attempts to examine the relationship between liberalisation of foreign purchase of properties and housing affordability in the presence of foreign direct investment (FDI) inflows. The negative relationship between liberalisation and affordability has caused dissatisfaction among Malaysians as house price has increased drastically since the government liberalise the foreign purchase of property. While Malaysia continues to receive FDI inflows which have been the engine for the country’s economic growth, it would be appropriate to examine the relationships between the liberalisation of purchase for properties by foreigners and the housing affordability within this context. Utilising the Johansen Cointegration method, this research analysed the long-term relationship of liberalisation of foreign purchase within the property sector and affordability of terrace houses. Through the use of the Channel method, this research also examines the role of FDI in the relationship.